In vitro fertilization (IVF) - De Valdivia Cano, Ramiro (2016)
A critical analysis is made of the interpretation that develops the Interamerican Court of Human Rights of the article 41 of the American Convention on Human Rights in the caseArtavia Murillo against Costa Rica about the legitimacy of in vitro fertilization, which according the Court‘s criteria would linked to rights to and to establish a family, in confrontation with the right to human life whose protection and recognition must be in accordance with the pro homine principle, by which the fundamental feature of human rights is to be always in favor of man, and that, as a consequence, the right to life must be respected from the moment of conception.